2008
DOI: 10.1111/j.1440-0960.2008.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of patch testing in patients with vulval pruritus

Abstract: SUMMARYForty-three patients with the primary complaint of vulval pruritus were recruited to take part in this prospective patch-testing study. A detailed questionnaire was administered to each and patch testing to an extended battery of allergens was undertaken. This included the European standard series, preservatives, corticosteroids and a battery of common over-the-counter topical vulval treatments. Analysis of demographic data and prior treatments used, and various other parameters, were studied in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 16 publications
4
48
2
3
Order By: Relevance
“…Those with vulval lesions alone had positive relevant findings in 19%, those with perianal disease alone in 33%, but those in whom both areas were involved there were positive relevant findings in 43%. A recent prospective study of 43 patients with vulval pruritus showed 44% to have relevant patch test reactions (Haverhoek et al 2008). In all studies, the relevant positive reactions were mainly to medicaments, local anaesthetics, corticosteroids and scented products.…”
Section: Allergic Reactions (Allergic Contact Dermatitis)mentioning
confidence: 96%
“…Those with vulval lesions alone had positive relevant findings in 19%, those with perianal disease alone in 33%, but those in whom both areas were involved there were positive relevant findings in 43%. A recent prospective study of 43 patients with vulval pruritus showed 44% to have relevant patch test reactions (Haverhoek et al 2008). In all studies, the relevant positive reactions were mainly to medicaments, local anaesthetics, corticosteroids and scented products.…”
Section: Allergic Reactions (Allergic Contact Dermatitis)mentioning
confidence: 96%
“…Studies report various results of positive reaction to patch testing, ranging from 16% to 78%. [34][35][36][37] This wide range is explained partially by different populations tested, either patients suffering from general vulvar pruritus, specific dermatoses or highly suspected of contact dermatitis, and whether the reaction measured was relevant to the clinical presentation. It is commonly agreed, that the rate of allergic and irritant contact dermatitis among patients suffering from vulvar symptoms is high, and it is not uncommon to find it complicating other established vulvar condition.…”
Section: Patch Testsmentioning
confidence: 99%
“…A prospective study showed a very high rate of contact sensitivity in patients presenting with vulval pruritus. One or more clinically relevant allergens were found in 44% of the subjects tested [5]. Many relevant allergens did not belong to the European standard series so there is a need for extended patch testing.…”
Section: Atopic and Contact Dermatitismentioning
confidence: 99%